Heart rate characteristic index monitoring for bloodstream infection in an NICU: a 3-year experience. Issue 4 (30th October 2015) - Coggins, Sarah A; Weitkamp, Jörn-Hendrik; Grunwald, Lisa; Stark, Ann R; Reese, Jeff; Walsh, William; Wynn, James L
Abstract : Background: Bloodstream infection (BSI) among neonatal intensive care unit (NICU) infants is a frequent problem associated with poor outcomes. Monitoring for abnormal heart rate characteristics (HRCs) may decrease infant mortality by alerting clinicians to sepsis before it becomes clinically apparent. Methods: HRC scores were acquired using the HRC (HeRO) monitor system from Medical Predictive Science Corporation and entered into the electronic medical record by bedside staff. We retrospectively analysed HRC scores recorded twice daily in the medical record during a 30-month period (1 January 2010 through 30 June 2012) for infants in the NICU at the Monroe Carell Jr. Children's Hospital at Vanderbilt. We identified infants that met Centers for Disease Control criteria for late-onset BSI (>3 days of life) during the study period. Results: During the study period, we recorded 127 673 HRC scores from 2384 infants. We identified 46 infants with BSI. Although 8% (9701/127 673) of the HRC scores were ≥2 and 1% (1387/127 673) were ≥5, BSI (at any time) was observed in just 5% of patients with HRC scores ≥2, and 9% of patients with HRC scores ≥5. Of infants with BSI, 5/46 (11%) had at least one HRC score ≥5 and 17/46 (37%) had at least one score ≥2 recorded in the 48 h period prior to the evaluation that resulted in the first positive blood culture of the episode. Conclusions: In our single-centre retrospective study, elevated HRC scores had limited ability to detect BSI. BSI was infrequent at any time during hospitalisation in infants with significantly elevated HRC scores.